20. UPAYA BNPT DALAM MELAKSANAKAN PROGRAM DERADIKALISASI DI INDONESIA - Fitriana, Saella; Utomo, Tri Cahyo; Pattipelohy, Shary Charlotte (Journal of International Relations, 2017)
Deradicalization program emerged from Indonesian government anxiety towards a high rateof radicalism and terrorism among civil society. Soft approach that became the cornerstone ofderadicalization program will be able to rehabilitate terrorist, its group, and family fromradical mindset effectively. They’re expected not to repeat the previous acts of terror, notback to being an agent of radicalism, and able to live in peace among others. Problems thenarise when the deradicalization program drawn criticism from several activists and religiouspractitioners group of civil society and rejection from the convict that said the program wasmade to discredit Islamic values. The purpose of this study is to describe and explaining theformulation of Indonesian deradicalization program in detail. This study uses a constructivistperspective and disengagement theory in explaining the formulation and implementation ofBNPT de-radicalization program. In this study, the author used qualitative methods withexplanatory research type, followed by collecting data through literature and interviewtechniques. Based on existing findings, the deradicalization program, which rooted inconstructivist basic assumptions and disengagement theory, is comprehensively establishedwithout discrediting certain religious values. And because terrorism in Indonesia is dominatedby radical Islamic thoughts, the implementation and approach of the deradicalization programare tailored to go harmoniously, to ensure the effectiveness of the rehabilitation program.